2019
DOI: 10.1093/bib/bbz126
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of differential splicing tools for RNA-seq studies

Abstract: Differential splicing (DS) is a post-transcriptional biological process with critical, wide-ranging effects on a plethora of cellular activities and disease processes. To date, a number of computational approaches have been developed to identify and quantify differentially spliced genes from RNA-seq data, but a comprehensive intercomparison and appraisal of these approaches is currently lacking. In this study, we systematically evaluated 10 DS analysis tools for consistency and reproducibility, precision, reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 52 publications
(81 reference statements)
7
102
0
Order By: Relevance
“…1a-b ). Importantly, this depth falls within the recommended depth (~60 million reads) for robust and reproducible splicing and differential expression analyses (Mehmood et al, 2019; Shen et al, 2012).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…1a-b ). Importantly, this depth falls within the recommended depth (~60 million reads) for robust and reproducible splicing and differential expression analyses (Mehmood et al, 2019; Shen et al, 2012).…”
Section: Resultsmentioning
confidence: 57%
“…Host splicing changes have been observed during infection with DNA viruses (HSV-1 (Hu et al, 2016), HCMV (Batra et al, 2016)) as well as RNA viruses such as reovirus (Boudreault et al, 2016), dengue virus (Sessions et al, 2013), and zika virus (Hu et al, 2017). However, these studies represent only the tip of the iceberg as they have mostly lacked the sequencing depth, and subsequent orthogonal validation, that is needed for a comprehensive quantitative analysis of host splicing (Mehmood et al, 2019; Shen et al, 2012)(Vaquero-Garcia et al, 2016). Therefore, we set out to comprehensively define the scope of host splicing changes during IAV infection in order to begin to address the underlying mechanisms and functional implications of such viral-induced alterations to the host transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to SplAdder, which is limited to the detection of simple types of splicing events, MAJIQ introduced a novel approach that additionally captures more complex transcript variations. MAJIQ was shown in a recent benchmark [31] to compare favorably to existing stateof-the-art methods and the authors demonstrated in [49] that MAJIQ also outperforms LeafCutter and rMATS.…”
Section: Resultsmentioning
confidence: 99%
“…However, a previous study showed that the use of ten differential splicing analysis tools resulted in the identification of different numbers of DAS genes. The number of identified DAS genes ranged from 0 (cuffdiff2) to 4506 (edgeR) in a human prostate cancer dataset, with 2962 and 0 DAS genes identified using rMATS in human and mouse datasets, respectively [49]. In addition, 252, 171, and 42 DAS genes were identified in comparisons between control and intolerant, control and tolerant and intolerant and tolerant catfish following heat stress [50].…”
Section: Discussionmentioning
confidence: 99%